2022
DOI: 10.1101/2022.08.14.503886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Interactions of Potassium Hydroxide in the Vicinity of Connective Disulfide Bonds of the Fab Regions of Some Human Immunoglubulins: Preliminary Computational Implications for Affinity on Cys-Cys Disulfide Bridges

Abstract: The average human lifespan continues to increase with the increase in data flow and the advancement of related technological developments. However, this development brings with it many diseases, including immunological problems. Immunoglobulin varieties found in different organisms in the last 3-4 decades continue to be hope for many diseases. Interest has focused on the lesser weight but more mobile immunoglobulins found in camelids. Later, different types of these antibodies were tried to be made with biotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…In another study with the KOH molecule, the affinity of KOH for disulfide bonds in some human immunoglobulins (Ig) Fab region was demonstrated by intermolecular interactions (27). These findings suggest that KOH potentially induces low-weight Ig production.…”
Section: Discussionmentioning
confidence: 99%
“…In another study with the KOH molecule, the affinity of KOH for disulfide bonds in some human immunoglobulins (Ig) Fab region was demonstrated by intermolecular interactions (27). These findings suggest that KOH potentially induces low-weight Ig production.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, there have been developments in the treatment of many diseases such as allergic, immunological, viral diseases or cancer. In the in silico study included in the discussion, it was found that the binding affinity of KOH to the region of the disulfide bonds between the heavy and light chain on the Ig structure with -1 kcal/mol increased up to the level of -3 kcal/mol with the increase in the number of KOH molecules [3]. The study showed the potential of this effect to form new small-weight Ig by breaking the disulfide bond between the heavy and light chains (Figure 1).…”
Section: Introductionmentioning
confidence: 99%